System for creating and authentication credentials - Abarca Rodrıguez, Marco Antonio; Nakano Miyatake, Mariko; Perez Meana, Hector Manuel (Visión electrónica, 2014)
This article present a system for creating and credential authentication personal identi- fication (ID) safe, using one-dimensional and two-dimensional barcodes, data encryption and symmetric key technique watermark. To do this, a watermark is inserted on the photo of the user, generated from a unique identification code which will be available in printed credential so that at the time of validation of the credential is carried by calculating the cross-correlation between the watermark contained in the photograph of the user and the watermark calculated at the time of validation using the same unique identification code. We show that proper selection of parameters for inserting the watermark: length, gain, position of the watermark and decision threshold, are essential to ensure the proper functioning of the proposed scheme, ensuring maintain sufficient quality in visual image to the user recognition and in turn be robust enough to withstand the attack of converting digital-analog (D / A) and analog-digital (A/D).